2020
DOI: 10.5027/jmh-vol18-issue1(2021)art99
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and consistency of movement behavior questionnaire (MBQ) in children at COVID-19 social distancing.

Abstract: Reliability and consistency of movement behavior questionnaire (MBQ) in children at COVID-19 social distancingFiabilidad y consistencia del cuestionario de comportamiento de movimiento (MBQ) en niños en distancia social COVID-19 Batista-Lemes, V 1 ; Felin-Fochesatto, C 2 ; Reis-Gaya, A 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 24 publications
2
32
0
7
Order By: Relevance
“…Of the studies, 37 used validated self-report measures of PA or related constructs, including the International Physical Activity Questionnaire (IPAQ), 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 PAQ-Adolescents, 67 , 68 , 74 , 75 Global-PAQ, 69 Godin Leisure Time Exercise questionnaire, 86 , 87 24-h PA recall, 88 , 89 Pediatric Functional Activity Brief Scale, 90 , 91 Youth Activity Profile Questionnaire, 70 ecological momentary assessments, 66 MoMo PA Questionnaire, 65 or other validated questionnaires. 73 , 92 Two studies designed and validated new questionnaires for children in lockdown, 93 , 94 and 3 studies used device-based measures of PA, including accelerometry 73 and pedometry. 95 , 96 Four studies used qualitative approaches, including interviews, 97 parent-to-child interviews, 98 open-ended questions, 92 and a case study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the studies, 37 used validated self-report measures of PA or related constructs, including the International Physical Activity Questionnaire (IPAQ), 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 PAQ-Adolescents, 67 , 68 , 74 , 75 Global-PAQ, 69 Godin Leisure Time Exercise questionnaire, 86 , 87 24-h PA recall, 88 , 89 Pediatric Functional Activity Brief Scale, 90 , 91 Youth Activity Profile Questionnaire, 70 ecological momentary assessments, 66 MoMo PA Questionnaire, 65 or other validated questionnaires. 73 , 92 Two studies designed and validated new questionnaires for children in lockdown, 93 , 94 and 3 studies used device-based measures of PA, including accelerometry 73 and pedometry. 95 , 96 Four studies used qualitative approaches, including interviews, 97 parent-to-child interviews, 98 open-ended questions, 92 and a case study.…”
Section: Resultsmentioning
confidence: 99%
“… 65 , 69 , 103 , 111 , 115 A large number of studies simply reported subjective changes of screen time or sedentary behavior. 72 , 78 , 84 , 100 , 101 , 103 , 114 , 117 , 119 , 141 , 146 Six studies implemented validated questionnaires that included sedentary behavior/screen time items, 66 , 70 , 93 , 94 , 104 , 147 and 4 studies 97 , 98 , 148 , 149 used qualitative approaches, including semistructured interviews, 97 , 148 focus groups, 149 and parent-to-child interviews. 98 …”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the prevalence of obesity rates which were already alarming tended to increase [ 20 ]. Another aspect contributing to this scenario was that the Physical Education classes were not applied in the school environment based on its traditional approach [ 17 , 18 , 21 24 ]. For example, Physical Education classes were done without an open sports court, involving a non-practical methodology with children alone at home.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Physical Education classes were done without an open sports court, involving a non-practical methodology with children alone at home. Given that context, it is difficult to establish high-intensity activities to promote an increase in physical fitness levels mainly because of motivational aspects [ 17 , 18 , 21 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation